2016
DOI: 10.1136/heartjnl-2016-310520
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast growth factor 23 as novel biomarker for early risk stratification after ST-elevation myocardial infarction

Abstract: Circulating FGF-23 is independently associated with LV remodelling after reperfused STEMI. A comprehensive multimarker strategy that includes FGF-23 provides incremental prognostic value for prediction of LV remodelling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
38
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 32 publications
1
38
0
Order By: Relevance
“…Additionally, FGF‐23 may downregulate soluble α‐klotho,34 an enzyme with anti‐aging effects that was shown to protect the heart against cardiac hypertrophy and cardiac remodeling 35, 36. In a study by Reindl et al, FGF‐23 was significantly higher in patients who developed LV remodeling post ST‐segment–elevation myocardial infarction even after adjustment for biomarkers of myocardial necrosis, myocardial stress, and inflammation 37. Finally, FGF‐23 may promote myocardial fibrosis through upregulation of β‐catenin, transforming growth factor‐β, procollagen I, and procollagen III, which may exacerbate diastolic dysfunction 38…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, FGF‐23 may downregulate soluble α‐klotho,34 an enzyme with anti‐aging effects that was shown to protect the heart against cardiac hypertrophy and cardiac remodeling 35, 36. In a study by Reindl et al, FGF‐23 was significantly higher in patients who developed LV remodeling post ST‐segment–elevation myocardial infarction even after adjustment for biomarkers of myocardial necrosis, myocardial stress, and inflammation 37. Finally, FGF‐23 may promote myocardial fibrosis through upregulation of β‐catenin, transforming growth factor‐β, procollagen I, and procollagen III, which may exacerbate diastolic dysfunction 38…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a risk score adding PWV to major clinical prognostic determinants of MACCE (age, NT‐proBNP, multivessel disease) was developed. As described in a previous study, 1 point was given for each of these parameters when they were above the optimal cutoff value derived from receiver operating characteristic analysis 18. This resulted in a score ranging from 0 to 4 points.…”
Section: Methodsmentioning
confidence: 99%
“…24, 25 Reindl et al showed in a recent study that the serum FGF23 level, measured 2 days after AMI onset, was associated with aggravated long-term LV remodeling, as assessed by cardiac magnetic resonance imaging and defined as at least a 20% increase in LV end-diastolic volume between the baseline scan and follow-up scan at 4 months. 12 As in the current study, they did not assess whether an elevated level of FGF23 predicted LV remodeling independent of other cardiac biomarkers or calcium/phosphate-related parameters, presumably because of the small sample size. Pöss et al showed that circulating FGF23 levels were higher among patients with cardiogenic shock than among those with uncomplicated AMI, which suggests that the serum FGF23 level may change according to the patient's physi-FGF23 in AMI log(relative FGF237d) significantly and negatively correlated with the change in LVEF between admission and 6 months afterward.…”
Section: Discussionmentioning
confidence: 99%
“…11, 12 Recent studies have shown that FGF23 is expressed and regulated in the heart and vessels. 13, 14 Notably, cardiac FGF23 expression and serum FGF23 levels were found to be increased in a rodent model of myocardial infarction (MI).…”
mentioning
confidence: 99%
See 1 more Smart Citation